ІSCHEMIC POSTCONDITIONING - Vatutin, N. T.; Kalinkina, N. V.; Bakhteeva, T. D.; Kolesnikov, V. S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Nowadays theraputical strategy of acute myocardial infarction includes both repefusion methods and treatment of consequences of blood flow restoring. This review presents recent data of literature on one of endogenous cardioprotection mechanisms, that preserves myocardium from ischemic and reperfusion damage ― ischemic postconditioning. Separately we marked at the history of investigation of this question. We examined processes, underlying this mechanism, triggers, that initiate it’s launch and its clinical perspectives.